The Source of Adolescents Reproductive Health Information and Dating Behavior Among Senior High School Students - Niken Meilani; Sunarru Samsi Hariadi; Fransiskus Trisakti Haryadi (Disease Prevention and Public Health Journal, 2023)
Background: The adolescence period is a crucial time for laying the foundations of good health. Having access to high Adolescents Reproductive Health (ARH) information decreases premarital sex, child marriage, adolescent pregnancy, Sexually-transmitted infections (STIs), and HIV/Aids. Premarital sex was associated with dating behavior. About 57% of adolescents have dating behavior. This study aimed to analyze the source of adolescents’ reproductive health related to dating behavior among adolescents. Method: This was a cross-sectional study carried out in July-September 2022. The study population was high school students in Yogyakarta. A multistage random sampling technique was employed, involving 80 respondents. The instrument used was a questionnaire that has been tested. Data analysis in chi-square and logistic regression using statistical test software. Results: Females (56.1%) and males (43.9%) had dating behavior. The father’s education (p=0.012), the mother’s communication about ARH (p=0.040), and the father’s communication about ARH (p=0.018) were related to dating behavior among adolescents. Father’s education affects dating behavior among adolescents OR 5.01. Adolescents who have a father who graduated >12 years of education were 5 times more likely to have no dating behavior. Conclusion: The role of parents is needed to prevent dating behavior among adolescents.